PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN FASILITAS SOSIAL TERHADAP KEPUASAN KERJA KARYAWAN KEBUN DI AFDELING 1 ESTATE TSB 1 PT. TRITUNGGAL SENTRA BUANA - Tantya Putri Andina; Ernita Obeth; Mujibu Rahman (JURNAL AGRIMENT, 2021)
This research is motivated by factors that affect employee satisfaction at work such as compensation provided by the company, the work environment created around the company and social facilities available in the company. Therefore, the purpose of this study was to determine the effect of compensation, work environment and social facilities on employee job satisfaction. This study obtained data through filling out questionnaires and interviews with 27 respondents. Data were analyzed using multiple linear regression, are T test to determine the effect of compensation, work environment, and social facilities partially on job satisfaction, F test to determine the effect of compensation, work environment, and social facilities simultaneously on job satisfaction, and R2 test to determine the contribution off all independent variables (compensation, work environment, and social facilities) to the dependent variable (job satisfaction). The results of this study indicate that only compensation and work environment have a significant effect on job satisfaction. The compensation value (t-count 2.67 > t-table 2.07) with a significance value of 0.013 < 0.05 and the value of work environment (t-count 3.52 > t –table 2.07) with a significance value of 0.001 < 0,05. The result of the F test indicate that compensation, work environment, and social facilities have a significant effect on job satisfaction (F-count 11.36 > F-table 3.03) with a significance value of F 0.00009 < 0.05. For the contribution or contribution of compensation, work environment and social facilities to job satisfaction, it shows a strong correlation with a percentage of 0.597 or 59.7%.